Population Dynamic, Anthelmintic Treatments and the Influence of Helminth Infections on Weight Gain in Water Buffalo Calves (Bubalus Bubalis) - Bastianetto, E.; Costa, J. O.; Guimarães, M.P.; Frei, C.M.V. (Journal of Buffalo Science, 2012)
The dynamics of gastrointestinal helminthiasis was studied in buffalo calves naturally exposed to helminth infection at two farms in Minas Gerais, Brazil. The effect of helminthiasis was evaluated with respect to weight gain of naturally infected untreated calves versus those which received anthelmintic treatment either with fenbendazole or ivermectin. The treated animals had significantly (p≤0.05) higher weight gain. Strongyloides papillosus was diagnosed from 30 to 60 days after birth, and Toxocara vitulorum from 60 to 90 days. During spring, there was a rise in the eggs per gram (EPG) count of Trichostrongylidae. Severe infection of Paracooperia nodulosa was detected in few 9-month-old buffalo calves.The results of this study indicate efficacy of fenbendazole and ivermectin in different age group calves for better health and reduced probability of helminth resistance. This study also indicates the necessity for good nutritional management of buffalo calves to improve the efficacy of parasite control.